2022
DOI: 10.1080/09638288.2022.2043464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of external lumbar supports on joint position sense, postural control, and postural adjustment: a systematic review

Abstract: Purpose: To review the effects of external lumbar supports on various aspects of sensorimotor function including joint position sense (JPS), postural control, anticipatory postural adjustments (APAs), and compensatory postural adjustments (CPAs). Methods: A systematic literature search was performed in PubMed, EMBASE, Scopus, Ovid, Cochrane library, and Web of Science. Two reviewers selected studies which assessed the effect of lumbosacral orthosis or kinesio-tape on JPS, postural control or APAs/CPAs in subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(243 reference statements)
0
4
0
Order By: Relevance
“…The limits of stability are important in KOA individuals to maintain a dynamic balance [22]. It is postulated that impaired joint position sense can reduce postural control, limit stability, and cause individuals to fall [23]. As knee proprioception, postural control, and limits of stability are significant factors that can significantly cause impairment, disability, and falls in individuals with KOA [21,24], it is essential to determine the magnitude of knee JPE and impairment to the limits of stability in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The limits of stability are important in KOA individuals to maintain a dynamic balance [22]. It is postulated that impaired joint position sense can reduce postural control, limit stability, and cause individuals to fall [23]. As knee proprioception, postural control, and limits of stability are significant factors that can significantly cause impairment, disability, and falls in individuals with KOA [21,24], it is essential to determine the magnitude of knee JPE and impairment to the limits of stability in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that patients with LBP have altered postural adjustment strategies and performance in voluntary postural tasks ( Azadinia et al, 2023 ; Rum et al, 2023 ). In this study, the LBP group showed lower AUC values on the SwayDA tests and performance in the mobility tests, and there was a positive linear association between the SwayDA tests and mobility tests.…”
Section: Discussionmentioning
confidence: 99%
“…An IPD meta-analysis enables calculating more precise estimates of effects (due to increased statistical power) [36][37][38][39][40], inclusion of explanatory covariates [36][37][38], adjustment for confounding factors [38][39][40], more powerful investigation of interactions [36][37][38]40], and exploring between-study heterogeneity [37,38,40]. Although prior systematic reviews have considered postural control among individuals with and/or without LBP during static/perturbed sitting [41][42][43][44], semi-sitting [41][42][43], standing [41][42][43][44][45][46][47][48][49][50][51][52][53][54], or walking [55], trunk postural control has not been evaluated in unstable sitting, and no reviews have used an IPD meta-analysis.…”
Section: Plos Onementioning
confidence: 99%